Stiffness, Vibration, and Strength of Flat Slab and Flat Plate Lightweight Concrete Slabs - Manar Zahid Zaman; Salah R. Al-Zaidee (Journal of Engineering, 2024)
Flat slabs made of two-way reinforced concrete are a common, effective, and affordable structural method. Thin layer slabs and lightweight are of great importance in modern building construction without the need to increase the cross-section of columns, walls, and foundations. Consequently, it becomes more important to cover all aspects related to stiffness, vibration, and strength of lightweight concrete slabs. To achieve serviceable flat slabs from lightweight concrete (LWC), the comparison between LWC flat plate and flat slab is studied in this article for strength and stiffness. The construction of the flat plate is much easier than other slabs even though the problem facing the flat plate is the punching shear. Hence, the addition of the drop panel as a solution. However, the two LWC slabs are exposed to a uniform pressure of dead load and human live load. The vibration of the slab is related to the stiffness in the form of the natural frequency. These floor systems should satisfy walking excitation criteria of acceleration limit , which is equal to 0.50% of g for office occupancies. This study aims to analyze a flat plate and flat slab with a drop panel for strength and stiffness. The analysis is carried out in ABAQUS software. The results of the analysis show that the flat slab has an effective increase in strength of about 60% compared to the stiffness which was lower by about 2.2 %. However, the stiffness of both slabs is within the limits of walking excitation criteria.